1996
DOI: 10.1021/je9501907
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic Conductivity of the N-Chloranil- and N-Xylylene-Based Polyelectrolytes in Dimethylformamide and Dimethyl Sulfoxide

Abstract: Electrolytic conductivities of four typical nitrogen-based polycations, where quaternary nitrogens in the molecular chain are attached with chloranil and xylylene moieties and are interspersed with ethylene, phenothiazine, and bipyridyl (viologen), linkages, have been investigated in dimethylformamide and dimethyl sulfoxide at 25 °C. The electrolytic conductivity as a function of concentration for systems with high charge density revealed a very narrow range of linearity in the dilute region. An empirical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…This typical behavior may be due to interactions within the molecule thereby causing constriction within the molecule or due to association between solute with solvent molecules. Similar behavior was observed by Singh et al 19,20…”
Section: Conductancesupporting
confidence: 89%
“…This typical behavior may be due to interactions within the molecule thereby causing constriction within the molecule or due to association between solute with solvent molecules. Similar behavior was observed by Singh et al 19,20…”
Section: Conductancesupporting
confidence: 89%
“…It is observed that for all the studied compounds, conductance increases with concentration in all the solvents. For dihydropyrimidinthiones compounds, conductance is lower in THF than that of DMF which may be due to greater electro relaxation effect owing to the higher permittivity of THF, which contributes interionic repulsions to a larger extent [24]. For dihydropyrimidine, conductivity is less in DMSO than that in DMF.…”
Section: Resultsmentioning
confidence: 98%
“…Singh et al prepared chloranil-based polyelectrolytes with a viologen and phenothiazine linkage. 39 Polyelectrolytes (P22a and P22b) were synthesized via Michael-type substitution− elimination between p-chloranil and tertiary amine/imine (Chart 6). The electrolytic conductivities of the polyelectrolytes were measured in DMF and DMSO.…”
Section: Polyelectrolytesmentioning
confidence: 99%
“…segments. These are derived mainly from polyviologens, 7 viologen-type building blocks, 35 quaternary ammonium-linked perylene units, 36 poly(pyridinium triflates), 37 aromatic ionenes, 38 and chloranil-based units 39 as the charged building blocks (Chart 3). These polyelectrolytes have applications in various fields, such as optoelectronic devices, DNA sensing, solar cells, and water splitting.…”
Section: ■ Introductionmentioning
confidence: 99%